Pengembangan E-Modul Berbasis Ethno-STEM Pada Bangunan Tradisional Uma Lengge Untuk Meningkatkan Kemampuan Representasi Matematis Siswa SMP - Andi Hasliyati Ike Safitri; Arnasari Merdekawati Hadi; Ilham Dwi Novaldin; Putri Agustina (Mandalika Mathematics and Educations Journal, 2025)
The development of digitalization technology in the world of education emphasizes the need for progressive learning innovation, not only focusing on procedural memorization, but it is important to integrate geometric concepts with cultural values ​​and STEM approaches. As for alternatives that answer these needs, the purpose of this study is to develop an Ethno-STEM based e-module that focuses on the Uma Lengge building as a geometry learning context to improve the mathematical representation abilities of junior high school students. In the development of this e-module, the ADDIE development model is used, which is Analysis, Design, Development, Implementation, Evaluation. In the data collection process by conducting observations, as well as using tests, andquestionnaires. The feasibility test obtained an e-module with a valid category in the material and design aspects, in addition, responses by students regarding the practicality of the module are in the practical category for use in learning, while the effectiveness test of the e-module showed an increase in students' representation abilities in the post-test results with a moderate to high increase, which indicates a significant difference from the pre-test results. So the Ethno-STEM based e-module focusing on the Uma Lengge building with the context of geometry material is effectively used to improve the mathematical representation abilities of junior high school students.